2021
DOI: 10.1111/ans.16708
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography‐measured body composition parameters do not influence survival in non‐metastatic colorectal cancer

Abstract: Background There is an increasing interest in studying the impact of altered body composition parameters and colorectal cancer (CRC) treatment outcomes. The aim of this study is to explore the impact of computed tomography (CT)‐measured visceral obesity, sarcopenia and myosteatosis on survival of non‐metastatic CRC. Methods Consecutive patients with stage I–III CRC who underwent curative‐intent treatment between January 2010 and December 2015 were included. By measuring the visceral fat area, and the skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
2
6
0
1
Order By: Relevance
“…In contrast, myosteatosis did not influence the NSC administration in RC patients. Interestingly, in a recent Latin-American-based study with non-metastatic CRC, body composition was not associated with survival outcomes (26), which corroborates the present results in the entire cohort. In aggregate, these data suggest that myosteatosis is a marker of postoperative frailty, which detects patients who performed worse during surgery and thus were unable to complete or even start adjuvant therapy, therefore jeopardizing the opportunity to offer patients a more satisfying quality of life and more prolonged survival.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, myosteatosis did not influence the NSC administration in RC patients. Interestingly, in a recent Latin-American-based study with non-metastatic CRC, body composition was not associated with survival outcomes (26), which corroborates the present results in the entire cohort. In aggregate, these data suggest that myosteatosis is a marker of postoperative frailty, which detects patients who performed worse during surgery and thus were unable to complete or even start adjuvant therapy, therefore jeopardizing the opportunity to offer patients a more satisfying quality of life and more prolonged survival.…”
Section: Discussionsupporting
confidence: 90%
“…Along these lines, some studies do not take into consideration the cancer clinical stage (CS), generalizing the findings to varying times of the diseases and outcomes ( 23 25 ). Furthermore, body composition studies in non-metastatic CRC rarely distinguish colon cancer (CC) and rectal cancer (RC) ( 15 17 , 21 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies are available on the prognostic utility of CT tissue density assessments in CRC patients. Two studies found that the low radiodensity of the muscle mass (i.e., higher fat content within muscle fibres) was associated with lower survival rates [ 19 , 20 ], while another study did not find a significant association after adjusting for other prognostic factors [ 21 ]. Only one study investigated the prognostic role of adipose tissue radiodensity in CRC patients, showing lower survival rates among patients with higher fat density (this may reflect both tissue inflammation and/or smaller or shrunken adipocytes, according to different hypotheses) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an association between sarcopenia with mortality, OS, recurrence-free survival, and postoperative complications. In this review, we found 13 studies 8 14 23 32 34 65 85 126 130 132 136 141 142 that reported on pancreatic and biliary malignancies and 31 studies 13 20 26 33 37 40 42 48 51 58 59 62 72 73 76 77 81 83 91 98 102 104 106 108 114 117 122 124 127 140 143 that reported on gastrointestinal and colorectal malignancies ( Tables 7 and 8 ).…”
Section: Introductionmentioning
confidence: 98%